Comparison of time-motion analysis and physiological responses during small-sided games in male and female soccer players - Jastrzebski, Z.; Radziminski, L.; Stepien, P. (Baltic Journal of Health and Physical Activity, 2016)
Background: The main purpose of this study was to compare the physiological response and time-motion analysis of male and female soccer players during 4 vs 4 small-sided games.